DOUBT AND DISENGAGEMENT: TECHNOLOGIES AND PRACTICES OF DIGITAL DISCONNECTION - Plaut, Ethan; Mannell, Kate; Kania-Lundholm, Magdalena; Beattie, Alex (AoIR Selected Papers of Internet Research, 2019)
When people distrust media systems, one response is to disconnect. This emergent theme within internet research encompasses technologies, practices, discourses, and politics of disconnection. Furthering these discussions, this panel draws together four investigations into technologies and practices of digital disconnection. Each paper interrogates a different form of disconnection and considers the various elements of trust and/or mistrust they reflect. Two of the papers focus on forms of disconnection centered around avoidance. One takes up the problem of digital propaganda and the associated declining trust in online media systems. It argues that informational avoidance in the form of ‘strategic illiteracies’ might open new spaces for resistance to misinformation. The other paper considers the challenge of managing personal availability in a context where mobile communication creates expectations of continual availability. It investigates the discursive practices that young adults use to avoid others and argues that these practices rest on implicit systems of trust. The remaining two papers consider how neoliberal discourses of self-improvement shape disconnective practices and technologies. They investigate forms of disconnection that are based around consumption choices and technology design. In both papers, disconnection is driven by growing distrust in dominant modes of technology design, specifically, their cognitive impacts. In response, the disconnective practices and technologies discussed in these papers place their trust in individualised, and often technological, solutions. Overall, the panel contributes to scholarly debate around disconnection by considering new forms of disconnection, their role in our contemporary media environment, and the forms of trust and mistrust they reflect.